(untitled) (Comparative & International Education Series, 2021)
As the world emerges from the COVID pandemic, it is good to remember the signs of hope that have been there all along from the small gestures of kindness to the heroic efforts of those on the frontlines, from strangers lifting their voices together in song across balconies as the pandemic began with the later Jerusalema dance challenge that swept around the world, even as the pandemic was raging. This pandemic has shown us that we are all truly interconnected, for better or for worse.